International trafficking in people for the purposes of sexual exploitation: a violation of the principle of human dignity (Research, Society and Development, 2022)
Trafficking in Persons is one of the most repugnant crimes and takes on transnational dimensions, in Brazil it is the country with the highest number of women who are trafficked with the intention of sexual exploitation in Latin America. Trafficking is present in history with its roots in slavery, a practice practiced all over the world and illegally. The beginning of the profitable practice of trafficking took place in Greece, Rome and Egypt, prisoners of war and women were exploited by the victors. In Brazil, trafficking marked history on blacks, in addition to manual slave labor, sexual service was also performed. Brazil stopped being a recipient and became one of the main suppliers of victims. Following the assumption that in Brazil, with the fragility of entry and exit of its citizens, looking to obtain financial improvement, women in particular accept the promises of life abroad, facing reality and not being able to afford their expenses, if subject them to prostitution, thus facilitating human trafficking. Being enshrined in the Federal Constitution, the dignity of the human person and based on bibliographic research, raises the questioning of the International Traffic in persons and the international protection of the Principle of Human Dignity, with the purpose of correlating the existing relationships between crime and the protection of individuals.